2016
DOI: 10.3389/fmicb.2016.01680
|View full text |Cite
|
Sign up to set email alerts
|

Is Penicillin Plus Gentamicin Synergistic against Clinical Group B Streptococcus isolates?: An In vitro Study

Abstract: Group B Streptococcus (GBS) is increasingly causing invasive infections in non-pregnant adults. Elderly patients and those with comorbidities are at increased risk. On the basis of previous studies focusing on neonatal infections, penicillin plus gentamicin is recommended for infective endocarditis (IE) and periprosthetic joint infections (PJI) in adults. The purpose of this study was to investigate whether a synergism with penicillin and gentamicin is present in GBS isolates that caused IE and PJI. We used 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…The reduction in bacterial load was minor after 3 days of treatment, irrespective of growth form and treatment regimen. At this measured time point, we observed – in line with our previous in vitro results ( Ruppen et al, 2016b ) – a significant difference in killing of transition-form GBS between PEN monotherapy and systemic PEN–GEN combination therapy, without fulfilling the criteria for synergism ( Figure 2A ). The difference between PEN monotherapy and systemic PEN–GEN combination therapy was not observed for assays with biofilm bacteria and not after 6 days of treatment.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The reduction in bacterial load was minor after 3 days of treatment, irrespective of growth form and treatment regimen. At this measured time point, we observed – in line with our previous in vitro results ( Ruppen et al, 2016b ) – a significant difference in killing of transition-form GBS between PEN monotherapy and systemic PEN–GEN combination therapy, without fulfilling the criteria for synergism ( Figure 2A ). The difference between PEN monotherapy and systemic PEN–GEN combination therapy was not observed for assays with biofilm bacteria and not after 6 days of treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The rationale for this combination therapy is a postulated synergistic effect ( Schauf et al, 1976 ; Deveikis et al, 1977 ; Cooper et al, 1979 ; Baker et al, 1981 ). In contrast to these study findings, the results of our recent experiments did not confirm a synergistic effect with planktonic GBS ( Ruppen et al, 2016b , 2017a ). In view of the potential nephrotoxicity of aminoglycosides and the increasing elderly population at risk for invasive GBS disease, the decision to administer or withhold aminoglycosides is of clinical relevance.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Recently, performed time-kill assays indicated that the addition of gentamicin to penicillin contributes to faster killing of planktonic GBS without fulfilling the criteria for synergism. The in vitro effect of faster killing was seen only at low penicillin concentrations and only within the first few hours of the assay [23]. When human blood products (serum, neutrophilic granulocytes, or whole blood from healthy volunteers [≥ 65 years]) were added to experiments, no beneficial effect of adjunctive gentamicin was seen [24].…”
mentioning
confidence: 99%